The Relationship Between Emotional Eating And Nutritional Status In Women Of Reproductive Age In The Rimau Islands, Sumur Village - Sofyan Musyabiq Wijaya; Ramadhana Komala; Sutarto Sutarto; Syahrul Hamidi Nasution (Poltekkes Kemenkes Mataram, 2023)
Background: The group of women of childbearing age is one of the phases to prepare a quality next generation. Inadequate food intake can cause problems with Chronic Energy Deficiency (KEK) in women of childbearing age. In women, the presence of depressive symptoms worsens the relationship between emotional eating and food intake. This study aimed to determine the relationship between emotional eating and the level of nutritional adequacy in women of childbearing age in the Rimau Islands, Sumur Village, South Lampung.Research Methods: This study used a cross-sectional or cross-sectional design. Researchers used the Dutch Eating Behavior Questionnaire (DEBQ), translated into Indonesian, specifically for Emotional Eating The nutritional status of young women can be seen from the Body Mass Index (BMI).Research Result: This study included 20 of the 30 respondents who attended. The statistical test for emotional eating on nutritional status (obesity) has no relationship with the p-value (0.766).Conclusion: This study concludes that there is no relationship between emotional eating and Nutritional Status.